Features of training programs of highly qualified athletes in cyclic disciplines, where the duration of competitive activity exceeds 6 minutes - Kryuchkov A.S.; Kryazhev V.D. (Theory and Practice of Physical Culture, 2025)
Objective of the study – is to establish the characteristics of the training work of the world's leading athletes specializing in sports disciplines where cyclical movements prevail and endurance is required. Methods and structure of the study.Theresearchmethodsused were the collection,systematizationandanalysis of materials from foreignscientificpapersextractedfrom the information and referenceresourcesGoogleScholarandPubMed.Thisarticlepresents the characteristics of the trainingload of highly qualifiedathletespracticingcyclicalsports. The distribution of trainingloadsbyintensitylevels is described.Thepercentagecontribution of trainingconductedineachof the intensityzones to thetotalannualtrainingcycleforvarioussportsdisciplines is reflected.Themaintrainingtoolsused by eliteathletesineachof the intensityzones are analyzed. Results and conclusions. For outstanding athletes competing in cyclical sports lasting more than six minutes, the total training time in the first intensity zone is 75-80% of the total training load during the one-year training cycle. 10-15% of training sessions are conducted in the moderate intensity zone. High-class athletes perform approximately 5-10% of the total annual volume with high intensity.